2013
DOI: 10.1186/1753-2000-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Parents of young people with self-harm or suicidal behaviour who seek help – a psychosocial profile

Abstract: BackgroundDeliberate Self-Harm (DSH) is a common problem among children and adolescents in clinical and community populations, and there is a considerable amount of literature investigating factors associated with DSH risk and the effects of DSH on the child. However, there is a dearth of research examining the impact of DSH on parents, and there are few support programmes targeted at this population. This cross-sectional study examines the profile of a sample of parents of young people with DSH who participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…For example, Coomber and King (2012) found that social support did not significantly predict or mediate caregiver burden for parents of children and young adults with eating disorders. Morgan and colleagues () found that the perceived social support for caregivers of young adults that deliberately self‐harm was not significantly correlated with parent well‐being. Determining the directionality and factors that link support seeking, stress, and self‐injury is a ripe area of inquiry for future study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Coomber and King (2012) found that social support did not significantly predict or mediate caregiver burden for parents of children and young adults with eating disorders. Morgan and colleagues () found that the perceived social support for caregivers of young adults that deliberately self‐harm was not significantly correlated with parent well‐being. Determining the directionality and factors that link support seeking, stress, and self‐injury is a ripe area of inquiry for future study.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Family financial problems (38) Parents with low well-being levels (52) Bad experience of family communication (52) Parents that live with or died of HIV/Aids (60) 26.4…”
Section: Family Relatedmentioning
confidence: 99%
“…After a suicide attempt, parents left without the needed support may contribute to the problem of adolescent suicide attempts. Morgan et al () found poor social support and poor parental well‐being were correlated with poor family communication, poorer parenting satisfaction, and a greater number of difficulties for children.…”
Section: Discussionmentioning
confidence: 99%